Effects of Al-Zahdi date palm seed extract on the AKT and PTEN genes expression in testicular tissues of mature and immature albino rats - Naziha S. Ahmed; Khalid K. Kadhim (Iraqi Journal of Veterinary Sciences, 2025)
This work was dedicated to the influence of oily and macerated Al-Zahdi date palm seed extracts (DPSE) on AKT and PTEN genes expression in testicular tissues and their relation to apoptosis. Sixty (30 mature and 30 immature) male albino rats were used for this study after being divided into six subgroups for each. Two subgroups were daily dosed with oily DPSE using two doses (200 and 400 mg/kg body weight) orally via micropipette over two successive months. Similarly, the other two subgroups were dosed with macerated DPSE, while the control received tap water. Expression of AKT and PTEN genes extracted from testis tissue was detected using the Preb Total RNA Extraction Kit. The Bcl-2 marker was tested using immunohistochemical staining to evaluate the incidence and spreading of the anti-apoptotic protein within the testis. Results revealed a significantly high expression of mRNA associated with both studied genes of both mature and immature rats treated with oily and macerated DPSE in comparison to control, with significant elevation of AKT level in oily treated rats, particularly with 4 hundred doses. Immunohistochemical results corroborated the genetic results as demonstrating a distinct presence of anti-apoptotic Bcl-2 in testicular cells, with greater clarity observed in mature testis, especially those treated with 400 mg/kg B. W. The study concluded that date palm seed extract acts as a natural stimulator for AKT in testicular tissue, which in turn contributes to prolonging the lifespan of testicular cells. Bcl-2 expression is present in testicular cells, with greater evidence in mature ones that received 400 mg/Kg.B.W.